2020
DOI: 10.3390/su12219264
|View full text |Cite
|
Sign up to set email alerts
|

Videogames and Innovation: Fostering Innovators’ Skills in Online-Learning Environments

Abstract: Innovation is quite important for economies and entrepreneurs around the world, especially for developing countries such as Colombia, where this study was based. Therefore, education for innovation becomes as important, and newer and innovative educational means must be adjusted for developing skills in innovation and entrepreneurship. Innovator’s DNA is a framework of skills that are meant to be developed by innovators. This framework proposes five discovery skills, which are: observing, associating, experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…Como ya se mencionó, en trabajos anteriores han intentado vincular el uso de los juegos serios con el desarrollo de las habilidades innovadoras, específicamente las descritas en el marco conceptual del ADN del innovador de Dyer y Christensen (2011), tal es el caso del videojuego CAFET, que consiste en un juego de cartas digitalizado, donde los jugadores-emprendedores interactúan alrededor de la industria del café, aunque este estudio solo se centra en las habilidades de observación, cuestionamiento y experimentación (Tobar-Muñoz et al, 2020).…”
Section: Resultados Preliminaresunclassified
See 1 more Smart Citation
“…Como ya se mencionó, en trabajos anteriores han intentado vincular el uso de los juegos serios con el desarrollo de las habilidades innovadoras, específicamente las descritas en el marco conceptual del ADN del innovador de Dyer y Christensen (2011), tal es el caso del videojuego CAFET, que consiste en un juego de cartas digitalizado, donde los jugadores-emprendedores interactúan alrededor de la industria del café, aunque este estudio solo se centra en las habilidades de observación, cuestionamiento y experimentación (Tobar-Muñoz et al, 2020).…”
Section: Resultados Preliminaresunclassified
“…Para iteraciones y pivotes futuros se sugiere aumentar el nivel de complejidad del prototipo, para que proporcione las entradas necesarias que faciliten la validación de la hipótesis. Sin embargo, se podría pensar que los juegos serios parecen ser un buen camino para desarrollar la habilidad de la innovación en los jóvenes, como un aporte de la tecnología en los procesos de enseñanza aprendizaje (Tobar-Muñoz et al, 2020).…”
Section: Resultados Preliminaresunclassified
“…While self-assessment scales are valuable, they may not capture the full spectrum of innovative thinking skills. As a result, the field is continually evolving to find comprehensive ways of understanding and assessing these vital capabilities, recognizing that they are not one-dimensional but multifaceted and interconnected (Barak & Yuan, 2021;Dyer et al, 2009;Schar et al, 2017;Strange, 2012;Tobar-Muñoz et al, 2020).…”
Section: Measurement Of Innovative Thinking Skillsmentioning
confidence: 99%
“…5. Idea networking refers to cooperation in exchanging knowledge to create and develop new knowledge (Dyer et al, 2009;Schar et al, 2017;Strange, 2012;Tobar-Muñoz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This is the case of the video game called CAFET which consists of a card game where players represent the entrepreneurs of the coffee industry in Colombia. Following this, a study [8] analyzed how video games can develop innovation skills and understand observed behaviours. The results showed that participants perform actions that can engage and develop the innovator's DNA skills, specifically observe, associate and experiment.…”
Section: Ainfluence Of Video Games On Educationmentioning
confidence: 99%